SISTEM PAGAR BERBASIS ARDUINO UNO DENGAN BLUETOOTH ANDROID APPLICATION - Leonard Tambunan; Muhammad Iqbal A.Tanjung (AMIK Mitra Gama, 2019)
Technology plane of electronic has influenced people’s lives to think practically and simply as a step to follow modernization. The role of high technology can be reducing the role of humans as subject of supporting facilities. The curren problem for access control is how to increase efficiency without reducing effectiveness in terms of operating the fence automatically to facilitate access control for motorist as acces users. Arduino UNO-Based Fence System With Bluetooth Android Application is a tool designed as an alternative to subject-based manual management to improve efficiency in terms of environmental safety. Principle of automatic fencing systems is the interaction of electronic component in the form of DC motor, HC-05, relay and switch with a microcontroller base the working principle includes the rotation of a DC motor as a fence drive rotor that acts as a fence pusher. With the input results sent via the Bluetooth application and processed throught the HC-05 module and controlled by Arduino UNO microcontroller as a programming language platform, the automatic system work system not reduce previous system reliability which manually based. Keywords: System, Modernisasi, Motor DC, Relay, Bluetooth, Microcontroller, Switch.